Pengaruh Citra Merek, Kualitas Produk, dan Celebrity Endorser terhadap Keputusan Pembelian Produk Erigo di Kota Medan - Dieri Apriana Purba; Anggiat Parlindungan; Suriyadi Suriyadi; Rismawati Rismawati; Nursiah Fitri (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Currently, people in buying fashion products prioritise ongoing fashion trends and generally like simple and casual fashion styles. In addition, in shopping, people prefer to buy local brand products rather than global because of the movement to love domestic products and local brand products are considered capable of rivalling the quality of international brands, this statement is a phenomenon in this study. One of these local fashion brands is Erigo. Erigo is widely known by the public and has even become the first rank of people's favourite local fashion brand. In Erigo products, there are several factors that influence consumers in making purchasing decisions, such as price, promotion, customer review, brand image, product quality, and celebrity endorsers. However, this study only examines the effect of brand image, product quality, and celebrity endorsers on purchasing decisions for Erigo fashion products in Medan City. This study uses quantitative research methods with descriptive research types which include validity tests, reliability tests, classical assumption tests, hypothesis tests (t tests, F tests, and coefficient of determination (R2) analysis tests). The analysis technique used is multiple linear regression analysis using the SPSS version 26 data processing programme with 100 respondents. The data collection technique used is the distribution of questionnaires via google form and literature study. Based on the research results, that brand image, product quality, and celebrity endorsers simultaneously and partially have a positive and significant effect on purchasing decisions. The determination test results show that the brand image, product quality, and celebrity endorser variables are able to explain 60.2% of the influence that occurs on the purchasing decision variable, while the remaining 39.2% is explained by other variables not examined in this study. In this study, the variable that has the most influence on purchasing decisions is celebrity endorser with a regression coefficient value of 0.308.